KEMUDAHAN PERIZINAN BERUSAHA PADA SEKTOR PERTAMBANGAN NIKEL DI INDONESIA PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA - Syukron Mahal Frawansa; Anna Maria Tri Anggraini (LPPM Universitas Ekasakti Padang, 2023)
Nickel mining activities include various stages, such as investigation, exploration, feasibility study, building, mining, processing, refining, transportation, and post-mining are all examples of mining operations. The government has the authority to manage nickel mining, but usually grants licenses to other parties to carry out mining activities. Law Number 11/2020 on Job Creation was introduced to simplify licensing and bureaucracy. The purpose of this study is to assess the influence of the law on the ease of business licencing and management of nickel mining in Indonesia. The research utilized both legal and non-legal materials and resulted in a descriptive and analytical juridical study. The study determined that nickel mining activities need a central government business licence, which is now simpler to obtain with a business identity number, standard certificate, and permission. The management of nickel mining following the passage of Law Number 11 of 2020 on Job Creation has had environmental and social consequences.